Latar Belakang Budaya dan Akuisisi Bahasa Pertama sebagai Kesalahan yang Mengganggu dalam Akuisisi Bahasa Kedua: Kasus Penulisan di Indonesia - Cesarandari, savira (Universitas Nusantara PGRI Kediri, 2019)
Abstract : Error Analysis is one of the major topics in the field of second language acquisition research. The learner of English as a second language is unaware of the existence of the particular system or rule in English language. The learner’s errors have long been interested for second and foreign language researchers. Some factors contributes in error of second language acquistion are habit formation relates to cultural background which bound their backgorund in education and another aspects. This paper attempts to investigate the notion of cultural background as the factors of errors in SLA which is the result of interference L1. The method that the researcher used is case study qualitative research, in which studying a phenomenon over time within its natural setting in one or a few sites. The result of the study indicates that cultural background, the society and education takes the big role in second language acquisition. The students with some English experiences even not native language, more adequate in comprehend the written form. Keywords : Error analysis, interference, second language acquisition